Pathophysiology of Acne Vulgaris: An Integrative Narrative Review - Malicka, Natalia; Tłustochowicz, Katarzyna; Łuczak, Karolina; Krajewska, Agnieszka; Korba, Magdalena; Polkowska, Wiktoria; Kowalik, Adrianna; Korzeniewska, Agnieszka; Dębczak, Julia (Quality in Sport, 2026)
Acne vulgaris is a common chronic inflammatory disorder of the pilosebaceous unit affecting all age groups. Its causes are complex and multifactorial involving skin microbiome changes, sebaceous gland hyperactivity, follicular hyperkeratinization, immune-mediated inflammation, hormonal signaling, and genetic susceptibility. Recent research shows acne is an immune-driven disease with early inflammation. This review provides an overview of acne pathophysiology focusing on interactions between inflammation, microbial imbalance, sebaceous gland activity, hormones, and genetics. A literature search was done using PubMed, Scopus, Web of Science, and Google Scholar from 2000 to 2025. Studies were analyzed to summarize molecular, cellular, and immune mechanisms in acne. Acne is driven by early persistent inflammation, altered sebum, microbial imbalance, especially pathogenic Cutibacterium acnes, and immune activation via Th1 and Th17 pathways. Androgens and IGF-1 modulate sebaceous glands and inflammation. Genetic factors influence immune response and sebaceous function. These mechanisms create a self-perpetuating loop causing lesion development. Acne is a multifactorial inflammatory disease from microbial, sebaceous, hormonal, immune, and genetic interactions. Understanding these pathways supports targeted therapies to reduce inflammation and restore microbial balance. Keywords – acne vulgaris, pathophysiology, inflammation, Cutibacterium acnes, sebaceous glands, androgens, IGF-1